Control of nanoscale precipitation and elimination of intermediate-temperature embrittlement in multicomponent high-entropy alloys. (1st May 2020) - Yang, T.; Zhao, Y.L.; Fan, L.; Wei, J.; Luan, J.H.; Liu, W.H.; Wang, C.; Jiao, Z.B.; Kai, J.J.; Liu, C.T.
Abstract: Thermally stable high-entropy alloys (HEAs) consisting of a high density of coherent precipitates show a great potential for high-temperature applications. In this work, we systematically investigated the phase stability and coarsening kinetics of L12 -type coherent precipitates in a Ni-30Co-13Fe-15Cr-6Al-6Ti-0.1B (at.%) HEA isothermally aged at 800, 900 and 1000 °C. Aged microstructures in the grain interiors under this temperature range were essentially dominated by the uniform precipitation of multicomponent L12 (Ni, Co, Fe, Cr)3 (Ti, Al)-type precipitates. The coarsening kinetics of these intragranular L12 precipitates were quantitatively determined, which were adequately characterized by the classical Lifshitz-Slyozov-Wagner model. The activation energy for coarsening was determined to be 378 kJ/mol, which is relatively higher than that of conventional Ni or Co-based superalloys, suggesting a slow elemental diffusion in the HEA matrix. More importantly, the heterogeneous precipitation and the associated metastable phase transformation mechanism along grain boundaries (GBs) were carefully analyzed. Localized chemical heterogeneity was identified within the discontinuous L12 phase at the GBs, which thermodynamically destabilizes the L12 structure and encourages the formation of brittle Heusler phase. Finally, we establish a unique duplex-aging strategy that can be efficiently utilized for GB stabilization, by which these detrimental intergranular heterostructures can be greatly eliminated, leading to an exceptional resistance to intermediate-temperature embrittlement, along with enhanced tensile strengths. These findings will not only shed light on the precipitation mechanisms in compositionally complex HEAs but also generate new opportunities to the interfacial design of HEAs for advanced high-temperature applications with superior properties. Graphical abstract: Image, graphical abstract